Characteristics of the national policies of the soviet regime in Lithuania from 1944 to 1953 - Pocius, Mindaugas (Genocidas ir rezistencija, 2010)
On the basis of the material documented in various archives and the latest historiography of Lithuania and other countries, this article seeks to research and summarise peculiarities and characteristics of the national policies of the Soviet regime in Lithuania between 1944 and 1953. The results of the primary research are provided and summarised. The author aims to provide answers to the questions of what factors, reasons, and circumstances determined national policies, what was characteristic to them, and what interests of the Soviet government can be discerned in them. The article reveals the Russification campaign and recruitment policy conducted by the Communist regime in Lithuania and describes the rather controversial policies of various periods with respect to Poles, the state anti-Semitic campaign, and the exiles of Germans. The author also focuses on the issue of the new national policies of Lavrentiy Beria. For the first time in Lithuanian historiography, Beria’s extremely valuable address of 8 May 1953 to Central Committee of the Communist Party of the Soviet Union about the political and public situation in the Lithuanian Soviet Socialist Republic is published.